2008
DOI: 10.1007/s00122-008-0813-4
|View full text |Cite
|
Sign up to set email alerts
|

The use of high resolution melting (HRM) to map single nucleotide polymorphism markers linked to a covered smut resistance gene in barley

Abstract: Using an established genetic map, a single gene conditioning covered smut resistance, Ruh.7H, was mapped to the telomere region of chromosome 7HS in an Alexis/Sloop doubled haploid barley population. The closest marker to Ruh.7H, abg704 was 7.5 cM away. Thirteen loci on the distal end of 7HS with potential to contain single nucleotide polymorphisms (SNPs) were identified by applying a comparative genomics approach using rice sequence data. Of these, one locus produced polymorphic codominant bands of different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 23 publications
0
37
0
1
Order By: Relevance
“…Allele-specific PCR assays were developed to enable direct selection of desirable fad2 and fad3 alleles in markerassisted trait introgression and breeding. In barley, SNP markers were identified that were linked to a covered smut resistance gene, Ruh.7H, by using high-resolution melting (HRM) technique [84]. In sugar beet, an anchored linkage map based on AFLP, SNP, and RAPD markers was developed to map QTL for Beet necrotic yellow vein virus resistance genes, Rz4 [85] and Rz5 [86].…”
Section: Examples In Othermentioning
confidence: 99%
“…Allele-specific PCR assays were developed to enable direct selection of desirable fad2 and fad3 alleles in markerassisted trait introgression and breeding. In barley, SNP markers were identified that were linked to a covered smut resistance gene, Ruh.7H, by using high-resolution melting (HRM) technique [84]. In sugar beet, an anchored linkage map based on AFLP, SNP, and RAPD markers was developed to map QTL for Beet necrotic yellow vein virus resistance genes, Rz4 [85] and Rz5 [86].…”
Section: Examples In Othermentioning
confidence: 99%
“…In this method, amplified DNA strands are melted apart via a gradual increase in temperature, and different melting patterns are detected based on subtle changes in fluorescence generated by double-stranded DNA-binding dyes. The rapid, inexpensive detection of a broad range of SNPs via HRM analysis makes this technique suitable for genotype discrimination (Lehmensiek et al 2008) and genetic mapping (Chagne et al 2008); various cultivars have been identified using SNPs via these technique (Mackay et al 2008). Therefore, in this study, we developed an effective method for identifying Korean-specific C. tricuspidata ecotypes using markers derived from plastid and nuclear DNA sequences and demonstrated that marker polymorphisms can be efficiently detected by ARMS-PCR and HRM analysis.…”
Section: Introductionmentioning
confidence: 99%
“…BRCA1 and BRCA2 genes, Hondow et al 2011). This method has also been used to detect mutations (single-nucleotide polymorphisms, SNPs and small insertions/deletions, InDels) in plant genetic studies, including TILLING in Lycopersicon esculentum (Gady et al 2009), Oryzias latipes (Ishikawa et al 2010), Triticum aestivum (Botticella et al 2011), Brassica rapa (Lochlainn et al 2011) and genetic mapping in Hordeum vulgare (Lehmensiek et al 2008), Zea mays (Li et al 2010) and Oryza sativa (Li et al 2011). HRM has also been used for the identification of transgenic plants (Milner et al 2014) and the detection of DNA methylation (Wojdacz and Dobrovic 2007).…”
Section: Introductionmentioning
confidence: 99%